2009
DOI: 10.1359/jbmr.081207
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Patients Have an Increased Risk of Vertebral Fractures Independent of BMD or Diabetic Complications

Abstract: Although patients with type 2 diabetes (T2DM) have an increased risk of hip fracture, risk of vertebral fracture (VF) and its association with BMD are still unclear. We examined Japanese T2DM patients (161 men >50 yr and 137 postmenopausal women) and non-DM controls (76 and 622, respectively) by lateral spine radiography and DXA at the lumbar spine (L), femoral neck (FN), and radius (R). Logistic regression analysis adjusted for age, body mass index, and L-BMD showed that the presence of T2DM was an independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
4
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(211 citation statements)
references
References 43 publications
8
188
4
11
Order By: Relevance
“…Patient histories of nonVFs that previously happened are also established risk factors for additional fractures [99]. We found that 38% of T2DM men and 31% of T2DM women had prevalent VFs by X-ray films, and that 16% each of T2DM men and women had histories of previous nonVFs [32]. Thus, if T2DM patients undergo spine X-ray examination or are questioned about their fracture histories, it is likely that about half of them are picked up as those who have bone fragility and need osteoporosis treatment for fracture prevention.…”
Section: Fracture Risk Assessment Of T2dm Patients In Clinical Prmentioning
confidence: 75%
See 1 more Smart Citation
“…Patient histories of nonVFs that previously happened are also established risk factors for additional fractures [99]. We found that 38% of T2DM men and 31% of T2DM women had prevalent VFs by X-ray films, and that 16% each of T2DM men and women had histories of previous nonVFs [32]. Thus, if T2DM patients undergo spine X-ray examination or are questioned about their fracture histories, it is likely that about half of them are picked up as those who have bone fragility and need osteoporosis treatment for fracture prevention.…”
Section: Fracture Risk Assessment Of T2dm Patients In Clinical Prmentioning
confidence: 75%
“…In contrast, it is little known about VF risk and its association with BMD. We examined Japanese T2DM patients and non-DM controls about this issue [31,32]. We found that the presence of T2DM was an independent risk factor for prevalent VFs in women [odds ratio (OR)=1.9] as well as men (OR=4.7) after adjustment for age, BMI, and lumbar BMD by logistic regression analysis.…”
Section: The Involvement Of Fat Tissue In Bone Metabolism Throughmentioning
confidence: 99%
“…(16) Another group reported that the presence of T2DM was an independent risk factor for prevalent VFs in Japanese men aged 50 years and older (OR, 4.73; 95% CI, 2.19 to 10.2) after adjusting for age, BMI, and lumbar spine BMD. (20) Because VFs are a major cause of pain and disability, (36,37) it is important to identify subjects at increased risk of VFs. In the present analysis, having diabetes was not statistically significantly associated with increased odds of prevalent or incident VFs.…”
Section: Discussionmentioning
confidence: 99%
“…(6,15,16) To date, information on VF risk in T2DM men is very limited and conflicting, and mostly based on prevalent VFs. (16)(17)(18)(19)(20) Thus, it is still not clear whether VF risk is increased in men with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…There is now a growing body of evidence that the incidence of these conditions is significantly increased in the presence of type 1 and 2 diabetes mellitus (DM) (1)(2)(3)(4)(5). Clinical data indicate that bone of diabetic patients is fragile and of poor quality, despite a bone mineral density (BMD) that is often normal.…”
Section: Introductionmentioning
confidence: 99%